2020
DOI: 10.1002/brb3.1980
|View full text |Cite
|
Sign up to set email alerts
|

Cycloid psychosis as a psychiatric expression of anti‐NMDAR encephalitis. A systematic review of case reports accomplished with the authors' cooperation

Abstract: Objective We reviewed the psychotic symptoms of anti‐NMDA receptor encephalitis (NMDARE) to differentiate its presentation from those found in a primary psychiatric disorder. We hypothesized that the cycloid psychosis (CP) phenotype would be a frequent clinical presentation in the psychiatric phase of NMDARE. Method A systematic literature review in PubMed of all case reports published on NMDARE was performed from database inception to March 2020. We included all cases where psychotic symptoms were reported an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We suggest that there are several reasons why prior knowledge may be challenged, thus, resulting in imprecise neurobiological encoding of priors (8). Specifically, imprecise encoding of prior knowledge may not only result from predominantly biological causes [e.g., anti-NMDA receptor antibodies in some psychotic states (28)], but also arise in complex situations characterized by threatening experiences and potentially uncontrollable social interactions as, e.g., experienced by previously traumatized or ethnically discriminated individuals (8,29). Previous studies found varying prevalence rates between 0 and 55% of PTSD in patients suffering from schizophrenia spectrum disorders (30), suggesting a rather high prevalence of PTSD which may often remain overlooked in clinical settings (31).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that there are several reasons why prior knowledge may be challenged, thus, resulting in imprecise neurobiological encoding of priors (8). Specifically, imprecise encoding of prior knowledge may not only result from predominantly biological causes [e.g., anti-NMDA receptor antibodies in some psychotic states (28)], but also arise in complex situations characterized by threatening experiences and potentially uncontrollable social interactions as, e.g., experienced by previously traumatized or ethnically discriminated individuals (8,29). Previous studies found varying prevalence rates between 0 and 55% of PTSD in patients suffering from schizophrenia spectrum disorders (30), suggesting a rather high prevalence of PTSD which may often remain overlooked in clinical settings (31).…”
Section: Introductionmentioning
confidence: 99%
“…However, one study argues that its psychiatric features meet the criteria for cycloid psychosis (CP). While not specific for anti-NMDAR encephalitis, CP delineates acute psychotic episodes with a fluctuant clinical pattern mostly characterized by confusion, psychosis, movement disorders (including catatonia) and oscillations of mood ( 8 ). Our patient displayed a triad of behavior alterations (with agitation and aggression), psychosis and catatonia.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated by our case, these psychiatric features develop rather sudden ( 1 ), while primary psychoses tend to have a more insidious onset. The course of the disease also differs; while psychiatric symptoms in anti-NMDAR encephalitis tend to fluctuate ( 8 ), they remain more stable in primary psychoses. Additionally, as in our case, the psychotic symptoms tend to be treatment-resistant which often require higher doses or combinations of antipsychotics ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…This has driven some authors to search for a specific psychiatric phenotype to identify AE patients during an early disease stage. Giné-Servén et al [17] propose cycloid psychosis (CP) as a risk psychiatric phenotype for anti-NMDAR encephalitis. CP is mainly characterized by an acute psychotic episode with a sudden onset and fluctuant clinical pattern with confusion, delusions, hallucinations, motility disturbances (including catatonia), and mood oscillations.…”
Section: The Current Role Of Csf Testing During Fep Evaluation In Cli...mentioning
confidence: 99%
“…CP is mainly characterized by an acute psychotic episode with a sudden onset and fluctuant clinical pattern with confusion, delusions, hallucinations, motility disturbances (including catatonia), and mood oscillations. While not specific for anti-NMDAR encephalitis, Giné-Servén et al [17] argue that identifying this risk phenotype in the early psychotic stage of the disease would ensure rapid diagnosis and initiation of treatment before the onset of neurological symptoms.…”
Section: The Current Role Of Csf Testing During Fep Evaluation In Cli...mentioning
confidence: 99%